PENGARUH KOMPENSASI DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI BAPPEDA KABUPATEN PANDEGLANG - Ulpah, Ulpah; Khaeruman, Khaeruman; Abduh, Edi Muhammad (Yayasan Education and Social Center, 2024)
Employee performance is the result of a person's efforts achieved through abilities and actions in certain situations. This research aims to determine the effect of compensation and work motivation on the performance of Bappeda Pandeglang Regency employees, both partially and simultaneously. The research method used is an associative quantitative method with probability sampling techniques, involving a population and sample of 57 employees. Data were analyzed using SPSS Version 26. The results showed that compensation had a significant influence on employee performance (H1) with a significance value of 0.000 < 0.05 and tcount > ttable (11.261 > 2.004). Work motivation also has a significant effect on employee performance (H2) with a significance value of 0.001 < 0.05 and tcount > ttable (3.487 > 2.004). Simultaneously, compensation and work motivation have a positive and significant effect on employee performance (H3) with a significance value of 0.000 < 0.05 and Fcount > Ftable (64,467 > 3.17). The conclusion of this research is that compensation and work motivation have a significant influence on the performance of Pandeglang Regency Bappeda employees, both individually and collectively